Peran Kepemimpinan Kepala Desa dalam Mengelola Sumber Daya Manusia (Studi Pada Desa Pucangtelu) - Zuli Kasmawanto (Universitas Islam Darul Ulum Lamongan, 2024)
Leadership plays a key role in human resource (HR) management, especially at the village government level. Effective leadership can increase the motivation, performance, and job satisfaction of village officials, as well as create a productive and harmonious work environment. The purpose of this study is to describe the capacity and competency development of village apparatus, work assessment and evaluation of village apparatus as well as motivation and job satisfaction of village apparatus. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with village heads, village secretaries, and other village officials, as well as through participatory observation and analysis of related documents. Improving the performance of village government is highly dependent on increasing the capacity and competence of village officials. The success of the development program is greatly influenced by efforts involving training, technical assistance, and knowledge exchange, as well as the support of village leaders' commitments, adequate budgets, and cooperation with third parties. To improve the performance of village government, work evaluation and evaluation of village apparatus are very important. The success of this process is greatly influenced by the methods used, clear assessment criteria, leadership participation, involvement of village officials, and the use of information technology. Various factors, such as awards, working conditions, leadership, relationships between colleagues, and work-life balance, affect the motivation and job satisfaction of village officials. Therefore, increasing motivation and job satisfaction must be the main concern in human resource management in village government.